2016
DOI: 10.1007/s00586-016-4555-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes between laminoplasty, posterior decompression with instrumented fusion, and anterior decompression with fusion for K-line (–) cervical ossification of the posterior longitudinal ligament

Abstract: LMP should not be used for K-line (-) cervical OPLL. ADF is one of the suitable surgical treatments for K-line (-) OPLL. Both ADF and PDF are applicable for K-line (-) OPLL according to indications set by each institute and surgical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 25 publications
3
108
0
Order By: Relevance
“…[7,912] Studies have shown poor clinical outcome after laminoplasty in patients with K-line (−) OPLL or thick OPLL (occupation ratio>60%). [7,11,13] However, retrospectively, we found that some of our patients with K-line (−) OPLL achieved satisfactory results after laminoplasty. In this study, the mean JOA score of the NEP group improved significantly, from 9.70 ± 2.16 before surgery to 12.50 ± 2.27 at the last follow-up ( P  = .014), with a mean recovery rate of 32.71 ± 40.45%.…”
Section: Discussionmentioning
confidence: 76%
“…[7,912] Studies have shown poor clinical outcome after laminoplasty in patients with K-line (−) OPLL or thick OPLL (occupation ratio>60%). [7,11,13] However, retrospectively, we found that some of our patients with K-line (−) OPLL achieved satisfactory results after laminoplasty. In this study, the mean JOA score of the NEP group improved significantly, from 9.70 ± 2.16 before surgery to 12.50 ± 2.27 at the last follow-up ( P  = .014), with a mean recovery rate of 32.71 ± 40.45%.…”
Section: Discussionmentioning
confidence: 76%
“…Along with that unstandardized reporting for quality and satisfaction of outcomes was also a limiting factor. Recent studies have also suggested that sagittal alignment may affect surgical outcome in degenerative cervical myelopathy for different approaches [36,37]. Based on a comparative analysis of three techniques, Koda et al [36] suggested that posterior or anterior decompression and fusion but not laminoplasty may be used for K-line cervical ossification of the posterior longitudinal ligament.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have also suggested that sagittal alignment may affect surgical outcome in degenerative cervical myelopathy for different approaches [36,37]. Based on a comparative analysis of three techniques, Koda et al [36] suggested that posterior or anterior decompression and fusion but not laminoplasty may be used for K-line cervical ossification of the posterior longitudinal ligament. The impact of preoperative sagittal alignment on postoperative outcomes in the present meta-analysis could not be assessed due to the nature of data reported by the included studies.…”
Section: Discussionmentioning
confidence: 98%
“…Posterior decompression and segmental fusion for the peak of OPLL segment is the other possible posterior surgical procedures for cervical OPLL. We apply long fusion because postoperative progression of kyphosis can cause insufficient spinal cord decompression [24]. However, there is a possibility that segmental fusion for OPLL peak level can improve clinical outcome and inhibit progression of OPLL.…”
Section: Discussionmentioning
confidence: 97%
“…Addition of instrumented fusion could suppress the progression of OPLL, however operative time and estimated blood loss increased. Thus we apply instrumented fusion not for prophylactics of OPLL progression but for kyphosis and/or thick ossification foci [24]. Posterior decompression and segmental fusion for the peak of OPLL segment is the other possible posterior surgical procedures for cervical OPLL.…”
Section: Discussionmentioning
confidence: 99%